Hepatoprotective and Neuroprotective Effects of Naringenin against Lead-Induced Oxidative Stress, Inflammation, and Apoptosis in Rats - Lubna A. H. Mansour; Gehad E. Elshopakey; Fatma M. Abdelhamid; Talat A. Albukhari; Samah J. Almehmadi; Bassem Refaat; Mohamed El-Boshy; Engy F. Risha (Biomedicines, 2023)
Naringenin (NRG) is one of the most important naturally occurring flavonoids, predominantly found in some edible fruits, such as citrus species and tomatoes. It has several biological activities, such as antioxidant, antitumor, antiviral, antibacterial, anti-inflammatory, antiadipogenic, and cardioprotective effects. The heavy metal lead is toxic and triggers oxidative stress, which causes toxicity in many organs, including the liver and brain. This study explored the potential protective role of NRG in hepato- and neurotoxicity caused by lead acetate in rats. Four groups of ten male albino rats were included: group 1 was a control, group 2 was orally treated with lead acetate (LA) at a dose of 500 mg/kg BW, group 3 was treated with naringenin (NRG) at a dose of 50 mg/kg BW, and group 4 was treated with 500 mg/kg LA and 50 mg/kg NRG for 4 weeks. Then, blood was taken, the rats were euthanized, and liver and brain tissues were collected. The findings revealed that LA exposure induced hepatotoxicity with a significant increase in liver function markers (p < 0.05). In addition, albumin and total protein (TP) and the albumin/globulin ratio (A/G ratio) (p < 0.05) were markedly lowered, whereas the serum globulin level (p > 0.05) was unaltered. LA also induced oxidative damage, demonstrated by a significant increase in malonaldehyde (MDA) (p < 0.05), together with a pronounced antioxidant system reduction (SOD, CAT, and GSH) (p < 0.05) in both liver and brain tissues. Inflammation of the liver and brain caused by LA was indicated by increased levels of nuclear factor kappa beta (NF-κβ) and caspase-3, (p < 0.05), and the levels of B-cell lymphocyte-2 (BCL-2) and interleukin-10 (IL-10) (p < 0.05) were decreased. Brain tissue damage induced by LA toxicity was demonstrated by the downregulation of the neurotransmitters norepinephrine (NE), dopamine (DA), serotonin (5-HT), and creatine kinase (CK-BB) (p < 0.05). Additionally, the liver and brain of LA-treated rats displayed notable histopathological damage. In conclusion, NRG has potential hepato- and neuroprotective effects against lead acetate toxicity. However, additional research is needed in order to propose naringenin as a potential protective agent against renal and cardiac toxicity mediated by lead acetate.